Evaluasi visual lanskap kawasan pesisir Muara Sungai Ayung Kota Denpasar - I Made Agus Dharmadiatmika; Anak Agung Keswari Krisnandika (ARTEKS : Jurnal Teknik Arsitektur, 2021)
The development of ​​ coastal areas in Denpasar City is no longer focused on one location in Sanur but rather prioritizes potential tourism areas such as the Ayung River Estuary in Kesiman Kertalangu Village. This area has a beautiful natural landscape which makes it a recreational destination for the surrounding community and several efforts have been made by the village government to make it desirable for tourists as observed in the evaluation of the beautiful landscape in Ayung river estuary to serve as an input for further planning of the area. This research was, therefore, conducted using a descriptive quantitative method and scenic beauty estimation for analysis. The results showed the high scenic beauty estimation category was on the west side of the Ayung River while the low category was in the coastal area to the north of the area. Moreover, the factors influencing the scenic beauty estimation value include vegetation, water elements, cleanliness, and the aesthetic form of hardscape/landscape elements.